Esensi Peserta Didik Dalam Perspektif Filsafat Pendidikan Islam - Rahmayani Siregar (Prodi PIAUD STAI Sumatera Medan, 2021)
This study aims to analyze the essence of students in the perspective of Islamic education philosophy both in terms of their potential and dimensions, the nature and responsibilities of students. The research method used is qualitative with a library research approach. The results of the study explain that the potential of students is wujdaniyah guidance, hisysyiyah guidance, aqliah guidance, dinniyah guidance, taufiqiyah guidance. while the physical dimension (physical), the intellectual dimension, the religious dimension, the moral dimension, the spiritual dimension (mental), the artistic dimension (beauty), the social dimension. The characteristics that must be possessed by students are to obey Allah SWT, prepare and purify themselves, expect Allah's pleasure, pray to Allah SWT, actualize practice. While the main task of students is to learn, study and practice knowledge in everyday life.